Dampak Kebijakan Pemerintah dalam Mendirikan Koperasi Desa Merah Putih di Kecamatan Sukodadi, Lamongan - Imam Syafi’i; Sofia Tri Septiawati (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
The establishment of the Red and White Village Cooperative (KDMP) is a strategic government initiative to empower the grassroots economy. In Lamongan, this program has shown significant progress, with 79% of villages having a cooperative legal entity. However, it still faces challenges such as legal hurdles and non-multifunctional business units. Therefore, this report recommends accelerating legalization, adopting business models integrated with local economic potential, and forging strategic partnerships as key steps to maximize the program's impact, especially in the Sukodadi sub-district, referencing a pilot study from Palembang. This analysis highlights that while the KDMP policy has made substantial headway in Lamongan by increasing the number of legally-recognized cooperatives, its full potential remains untapped due to administrative bottlenecks and a lack of business model diversification. The successful model from Palembang, which includes digitalization and partnerships with banks, serves as a crucial benchmark for what is possible. By focusing on streamlining legal processes and fostering an environment for strategic collaboration and innovation, the cooperatives in Lamongan can evolve from simple grocery stalls into multifaceted economic hubs that truly empower the local community and align with the program's broader vision.